Architectural recycling. Case: urban regeneration area of Portoviejo - Lozano Molina, María (2024)
In this research, an intervention proposal is presented in the field of architectural recycling, which has been developed specifically for Ground Zero of the city of Portoviejo. One of the highlights in this study was the identification of a selection process that allowed the building to be chosen that met the necessary requirements to become the ideal project for its development. An exhaustive analysis was carried out on each element that makes up the Amen House, from its history to its functions and its current physical state. A major challenge in this proposal was the fact that the house is listed as a City Heritage Site, implying the need to carefully preserve its distinctive features. As a result of this detailed analysis, a proposal was formulated to revitalize and extend the useful life of this building.